Chromium propionate supplementation alters animal growth performance, carcass characteristics, and skeletal muscle properties in feedlot steers. Issue 3 (30th July 2020) - Baggerman, Jessica O; Smith, Zachary K; Thompson, Alex J; Kim, Jongkyoo; Hergenreder, Jerilyn E; Rounds, Whitney; Johnson, Bradley J
Abstract: The objective of this study was to evaluate the effects of increasing concentrations of Cr propionate (CrP) on feedlot performance, blood parameters, carcass characteristics, and skeletal muscle fiber properties in feedlot steers. Crossbred steers ( n = 32; 367 ± 2.5 kg; 16 pens; 2 hd/pen) were blocked by body weight (BW), and treatment was randomly assigned to pen: (1) 0 mg added Cr/kg diet dry matter (DM) (control), (2) 0.15 mg added Cr/kg diet DM (CrP; KemTRACE Chromium 0.04%, Kemin Industries, Des Moines, IA), (3) 0.30 mg added Cr/kg diet DM, and (4) 0.45 mg added Cr/kg diet DM. Steers were fed ad libitum, and the treatment was top-dressed at the time of feeding. Body weights, blood samples, and longissimus biopsies were collected before feeding on days 0, 28, 56, 91, 119, and 147. Blood sera were harvested for analysis of glucose, insulin, sera urea nitrogen, and non-esterified fatty acid concentrations. Longissimus biopsies were collected for gene expression, protein expression, and immunohistochemical (IHC) analysis. Pen was the experimental unit for live and carcass data, and steer was the experimental unit with day as a repeated measure for sera and IHC analyses. For the entire duration of the trial, a linear increase in average daily gain (ADG) ( P = 0.01) and improvement in G:F was observed ( P = 0.01) with no change in DMI ( P = 0.11) with increasing CrP. A linear increase in hot carcass weight (HCW) ( P ≤ 0.01) with no other changes in carcass composition were noted ( P ≥ 0.38) as the level of dietary CrP increased. There was no effect of treatment on any sera parameters measured ( P ≥ 0.10). No difference was detected for gene or protein expression of glucose transporter type 4 (GLUT4) due to CrP supplementation ( P ≥ 0.10). For skeletal muscle fiber distribution and cross-sectional area, there was no effect of treatment ( P ≥ 0.10). Density of total GLUT4 did not change due to CrP ( P ≥ 0.10). Internalization of GLUT4 was increased in the 0.30 and 0.45 mg/kg treatments ( P < 0.01). For total nuclei density and myonuclei density, there were treatment × day interaction tendencies ( P ≤ 0.08). Supplementation of CrP did not alter density of satellite cells ( P ≥ 0.10). The number of transporters located in the sarcolemma of skeletal muscle fibers did decrease, implying fewer proteins were needed to transport extracellular glucose into the muscle fiber. Therefore, CrP may augment cellular function and growth via increased efficiency of GLUT4 function. These results indicated CrP increases BW, ADG, and HCW, without changes in circulating sera parameters or total GLUT4 expression.